Criteria and indicators for sustainable forest management: new findings from CIFOR's forest management unit level research - Prabhu, Ravi; Colfer, C.J.P.; Shepherd, G. (1998)
This paper traces the growing interest in the development of Criteria and Indicators for sustainable forest since the declaration of the 'Forest Principles' at the Rio Conference 1992. Several processes are underway in the different regions of the world to define sets of criteria and indicators that can be used to assess the social, economic, and ecological sustainability of forest management. Some have focused more at national level, while others have emphasised information needs at the forest management unit level. In an attempt to produce a generic 'master set', the Center for Internetional Forestry research (CIFOR) has carried out several tests to compare the different sets of criteria and indicators currently existence. At the forest level, ecological criteria have been found much easier to apply than social ones as the latter often require an in-depth understanding of areas beyond the intermediate boundaries of the forest management unit. In an attempt to help people in different areas adapt the generic hierarchy of criteria and indicators to their own conditions, CIFOR is developing a computer programme, CIMAT, which allows for the addition of local knowledge and an iterative development of locally-specific criteria and indicators. In spite of the work still needed, the importance of defining a comprehensive but practical set of criteria and indicators lies in the fact that such a measurable and comparable methodology would build public confidence in the issue of forest sustainability.